Buzz - Spinelli, Eileen; Nguyen, Vincent (New York : Simon & Schuster Books for Young Readers, 2010)
After learning that a bee's body is too chunky for flight, Buzz the bumblebee defies the laws of aerodynamics to save a friend in need.
Booklist
Booklist, June 2010
2.5
K-3.
K-3
Keywords: Animals -- Juvenile fiction; Bumblebees -- Juvenile fiction; Flight -- Juvenile fiction; Animals -- Fiction; Bumblebees -- Fiction; Flight -- Fiction; Animals -- Fiction; Bumblebees -- Fiction; Flight -- Fiction; Picture books for children